The Strategic Dimensions of Experience-Based Tourism Marketing and its Impact on Enhancing the Digital Reputation of Destinations (Comprehensive Journal of Science, 2026)
This research aims to investigate the strategic and organizational dimensions of experiential tourism marketing and its role in enhancing the digital reputation of tourist destinations in the cyber era. The research problem stems from the organizational failure to transform real-world tourism experiences into strategic tools capable of building a strong mental image in cyberspace, coupled with an over-reliance on traditional promotional methods that lack digital credibility. The study adopted a descriptive-analytical approach, utilizing a documentary survey of modern literature and theories in the experience economy, alongside a qualitative digital content analysis of leading global platforms.The research concluded that the digital reputation of a tourist destination is primarily shaped through the spontaneous documentation by tourists, fueled by the sensory and aesthetic dimensions of the experience. Furthermore, emotional and social engagement with local communities contributes to transforming the tourist from a passive consumer into a digital advocate and a reputation guardian against information crises, thereby enhancing digital trust and transparency. The results also indicated that the experience economy provides destinations with a sustainable competitive advantage by reducing traditional advertising costs and relying on user-generated content as powerful social proof. The study recommended the necessity of redesigning tourism environments to be digitally stimulating, investing in sentiment analysis technologies to ensure proactive digital reputation management, and empowering local communities to create the human stories that grant the destination its authentic character within the virtual world.